Gnostik Geleneğin Erken Dönem Şiilikteki Tezahürleri: Şiî Gulat Örneği - Koçak, Yusuf (Oku Okut Yayinlari, 2021)
This study mainly investigates the gnostic tradition and its first manifestations in Shiism and their historical roots. The study covers the first and second centuries of Hijra. In the research, the earliest works on the subject are used as primary sources, as well as second-hand sources. The works examined are in Arabic, English, German and Turkish. It is seen that the Gnostic tradition is neglected in the studies on the Shiite-Ghulat. The importance of this study reveals itself at this point. With this study, an unknown dimension of Ghulat has been clarified by examining the Gnostic aspect of Shiite-Ghulat that has not been studied before. In this study, the epistemology of Shiite-Ghulat thought and its sources have been tried to reveal. While doing this, it is aimed to identify the ancient roots of the Gnostic tradition and to reveal how it affected the Shiite understanding. In this framework, an unknown and unstudied dimension of Shiism is clarified. In the research process, firstly, it is investigated how the subject is reported in the main sources of History of Islamic Sects and in the works written in the following period. Additionally, it is not satisfied only with the horizontal comparison between the early Shiite sources and other sources written in the same period, but also a vertical comparison in which the information in the recent works is compared is included. The obtained data are analyzed in line with the aims of the study. Since this study is a narration-centered research, methods for the evaluation of narrations are also used. In this context, reference is made to the books of Rijāl, Tabaqāt and Maqālāt. In this study, a descriptive, analytical and comparative approach is used in general. Gnosticism, which has a peculiar understanding of God, the idea of ​​the creation of the universe and man, and the idea of Gnostic knowledge that is claimed to lead to salvation, influenced Indo-Persian thought, Neoplatonism, Hermeticism, Judaism, Christianity, Sabianism, Manichaeism and many religious and philosophical movements throughout history. The religions and currents influenced by Gnosticism mainly existed in and around today’s Middle East, where three continents intersect. These religions and currents, which have existed in this geography for centuries, have been influenced by each other in the historical process, and have been in mutual interaction with the Muslims after the Muslims conquered that geography. In this sense, the transference of Gnostic thought to Muslims was not through a single channel like Neoplatonism or Hermetic thought, but rather through syncretic structures such as Nestorianism and Jacobites, sub-branches of Syriac Christianity, which harmonized Christianity, Neoplatonism, Hermetic and Gnostic thoughts. Gnostic thought firstly influenced the Shiite Ghulat Kaysāniyya and its sub-branches Bayāniyya, Mughīriyya, Masnūriyya, and Khattābiyya in Islamic thought.
Keywords: Social sciences (General); H1-99; Gnostisizm; Şia; Gulat; Nesturi; İslam Mezhepleri Tarihi; Yakubi